Contribution of Acute-Phase Proteins and Cardiovascular Risk Factors to Erythrocyte Aggregation in Normolipidemic and Hyperlipidemic Individuals - Weng, Xiaoduan; Roederer, Ghislaine O.; Beaulieu, Raymond; Cloutier, Guy (Thrombosis and Haemostasis, 1998)
Background. Numerous studies have demonstrated that elevated concentrations of acute-phase proteins affect red blood cell (RBC) aggregation. Plasma lipids and lipoproteins were also shown to be correlated with RBC aggregation in hypercholesterolemia. However, whether acute-phase proteins promote RBC hyperaggregation in hyper-lipidemic patients is unknown. The main objective of the study was to identify the impact of acute-phase proteins such as fibrinogen (Fib), haptoglobin (Hp), ceruloplasmin (Cp), α1-acid glycoprotein (AGP), α1-antitrypsin (AT), immunoglobulin G (IgG), and albumin (Alb) on RBC aggregation in 35 hyperlipidemic patients. The influence of these proteins in 32 normolipidemic subjects was also determined.Methods and Results. RBC aggregation parameters reflecting the kinetics of rouleau formation and the adhesive strength between RBCs were measured by laser reflectometry. Multivariate forward stepwise linear regression analyses were performed to study the relationship between RBC aggregation and these acute-phase proteins, total cholesterol (TC), triglycerides (TG), high (HDL-C) and low (LDL-C) density lipo-protein cholesterol, age, gender, body mass index (BMI), mean blood pressure (Mpressure), and smoking habit. The kinetics of rouleau formation was positively correlated with the linear combination of IgG and Hp (r = 0.76, p <0.0001) in hyperlipidemic patients, whereas IgG, smoking, AGP and gender were significant independent predictors in healthy subjects (r = 0.79, p <0.0001). The correlations obtained for the models predicting the adhesive strength between RBCs were 0.69 in patients (Alb, HDL-C, IgG, p <0.002) and 0.71 in healthy individuals (AGP, BMI, p <0.0001).Conclusion. This study suggests that acute-phase proteins such as IgG, Hp, AGP and Alb influence significantly and in an independent way the level of RBC aggregation. The close association between RBC aggregation and cardiovascular risk factors further strengthens its clinical importance.